x=1, x=-1, x=-3

Factors: (x-1)=(x-1)

(x-(-1))=(x+1)

(x-(-3))=(x+3)

f(x)=a(x-1)(x+1)(x+3)

From graph f(0)=-3

f(0)=a(0-1)(0+1)(0+3)=-3

-3a=-3

\(\displaystyle{x}^{{2}}+{3}{x}^{{2}}-{x}-{3}\)

f(x) on \(\displaystyle{y}{\left({x}\right)}={x}^{{3}}+{3}{x}^{{2}}-{x}-{3}\)

Factors: (x-1)=(x-1)

(x-(-1))=(x+1)

(x-(-3))=(x+3)

f(x)=a(x-1)(x+1)(x+3)

From graph f(0)=-3

f(0)=a(0-1)(0+1)(0+3)=-3

-3a=-3

\(\displaystyle{x}^{{2}}+{3}{x}^{{2}}-{x}-{3}\)

f(x) on \(\displaystyle{y}{\left({x}\right)}={x}^{{3}}+{3}{x}^{{2}}-{x}-{3}\)